2022
DOI: 10.18332/tid/144230
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette knowledge, attitudes and use among students at a university in Hangzhou, China

Abstract: INTRODUCTION Electronic cigarettes are increasingly popular worldwide, especially among youth. There is growing evidence of the negative health consequences of vaping. Our objective was to assess university students' knowledge and attitudes regarding electronic cigarettes (e-cigarettes), their use, as well as the associated influencing factors for their use. METHODS The study involved an online cross-sectional survey conducted between November 2019 and March 2020 in a university in Hangzhou, China. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 24 publications
5
13
5
Order By: Relevance
“…Another study by Gorini et al, (2020) in Italy stated that the prevalence of vaping device users in 2018 has reached 17.5%. However, this was lower than the percentage of e-cigarettes users in a previous study in China, where only 8.2% of the students indicated they had ever used an e-cigarette (Fang et al, 2022). E-cigarettes are being advertised as a safer alternative to cigarettes, an effective tool for quitting smoking and a device that may be used in places where smoking is not permitted.…”
Section: Medical Science L Analysis Articlecontrasting
confidence: 65%
“…Another study by Gorini et al, (2020) in Italy stated that the prevalence of vaping device users in 2018 has reached 17.5%. However, this was lower than the percentage of e-cigarettes users in a previous study in China, where only 8.2% of the students indicated they had ever used an e-cigarette (Fang et al, 2022). E-cigarettes are being advertised as a safer alternative to cigarettes, an effective tool for quitting smoking and a device that may be used in places where smoking is not permitted.…”
Section: Medical Science L Analysis Articlecontrasting
confidence: 65%
“…A cross-sectional questionnaire was developed based on an intensive review of the available literature [ 11 , 13 , 17 , 18 ]. The tool was constructed to study the prevalence of e-cigarette use as well as the knowledge about and attitude toward e-cigarettes among the students from health professions at the University of Jordan (UJ).…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of knowledge score calculations, the correct answer was coded as 1, and the incorrect or “I don’t know” answers were coded as 0 as both answers indicate a lack of knowledge. The last section was composed of items concerning the attitude of study participants toward e-cigarettes using the scale that was developed and validated by Fang et al in 2022 [ 13 ]. The original scale was published in English and consists of 19 items with a five-point Likert scale response that ranges from strongly disagree to strongly agree.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, most student pharmacists in this study correctly answered items about the marketing of e-cigarette/vape products. This is interesting given that a previous study conducted in Egypt among healthcare professionals and the general population found that media advertisements were the main source of information about electronic cigarettes [ 16 ]. These findings suggest that the marketing of e-cigarette/vape products may be influential in people’s knowledge regarding the perceptions of these products.…”
Section: Discussionmentioning
confidence: 99%